Parteienpositionen: Annäherung in der Mitte und zunehmende Distanz zur AfD - Richard von Maydell (Wirtschaftsdienst, 2024)
As fringe parties increasingly capture a larger portion of the votes, the issue of how centrist parties can set themselves apart from these extremes while establishing distinct characteristics has become more prominent in public and political debates. Despite analyses of programmatic overlaps between various parties indicating a separation of centrist parties from the far-right AfD (Alternative for Germany), there is no clear evidence that centrist parties hold uniquely defined stances among themselves. In this context, we have not observed a sharpening of the programmatic profiles of centrist parties since 2002.
Keywords: D72; H11; 330